Visi Pemimpin Pendidikan Berbasis Agama, Filsafat, Psikologi dan Sosiologi - Cecep Tatang Wijaya; Dadang Suparman; Neng Hilma Mimar (Universitas Islam Bunga Bangsa Cirebon, 2021)
Visionary leadership is leadership that puts forward the implementation of the vision for the advancement of education not only in the present but also in the future. So the visionary leader must have a big idea to advance his institution through a strong vision and mission. The purpose of this study is an educational leader who has a vision, good insight based on religion, philosophy, psychology and sociology that can improve the quality of education. This research is structured with a deductive approach, namely through the literature study method, either in books, journal articles, or online that discuss educational leadership. The results of the research Visionary is one of the characteristics of a leader. Reactive leaders are leaders who have a tendency to think only for the short term in achieving a goal. And this principle is the very opposite of the visionary meaning. Leaders without visionaries are the same as leaders who are reactive. Because the character of a leader who has a reactive nature is a leader who focuses on working quickly to respond to all actions, but the results are not effective, they are only oriented to all things that are zhaa'hiriyyah (visible), namely this place and in the present time. In contrast to visionary leaders, they always prioritize organizational management based on plans that are new and dynamic and think about the future, on the other hand, the characteristics of managers are those who prioritize maintaining organizational performance stability. Visionary leadership is characterized by the ability to manage intuition related to the focus of institutional development and the educational environment, the ability to manage the vision of an educational organization to measure ideas that contain ideal scenarios about the future and the reality that has been realized or not, and the ability to analyze challenges and obstacles as strengths and weaknesses. opportunities based on leadership research that have made progress. ABSTRAK Pemimpinan visioner merupakan kepemimpinan yang mengedepankan implementasi visi untuk kemajuan pendidikan bukan hanya di masa kini namun juga di masa yang akan datang. Sehingga pemimpin visioner harus mempunyai sebuah gagasan besar untuk memajukan lembaganya melalui visi dan misi kuat. Tujuan penelitian ini adalah seorang pemimpin pendidikan yang mempunyai visi, berawasan yang baik berlandaskan pada agama, filosofi, psikologi dan sosiologi yang dapat meningkatkan mutu pendidikan. Penelitian ini disusun dengan pendekatan deduktif yakni melalui metode studi kepustakaan, baik pada buku-buku, artikel jurnal, atau pada online yang membahas mengenai kepemimpinan pendidikan. Hasil penelitian Visioner merupakan salah satu karakteristik pemimpin. Pemimpin yang reaktif adalah pemimpin yang mempunya kecedrungan berpikir hanya untuk jangka pendek dalam mencapai sebuah tujuan. Dan prinsip ini sangat berlawanan dengan makna visoner. Pemimpin tampa memeliki visioner sama dengan pemimpin yang bersikap reaktif. Karena karakter pemimpin yang memiliki sifat reaktif adalah pemimpin yang fokus bekerja cepat untuk merespon semua tindakan, namun hasilnya tidak efektif, mereka hanya berorientasi pada segala hal yang zhaa’hiriyyah (kasat mata), yaitu tempat ini dan dalam waktu sekarang. Berbeda dengan pemimpin yang visioner, mereka selalu menegedepankan pengelolaan organisasi berdasarkan rencana-rencana yang bersifat baru dan dinamis serta berpikir masa depan, sebaliknya karakteristik mananjer adalah yang mengedepankan dalam menjaga stabilitas kinerja organisasi. Kepemimpinan visioner ditanda oleh kemampuan mengelola intuisi yang berhubungan dengan fokus pengembangan lembaga dan lingkungan pendidikan, kemampuan mengelola visi organisasi pendidikan untuk mengukur gagasan-gagasan yang mengandung skenario ideal tentang masa depan dan kenyataan sudah terwujud apa belum, dan kemampuan menganalisa tantangan dan hambatan menjadi kekuatan dan peluang berdasarkan riset kepemimpinan yang berhasil mencapai kemajuan.